Current Issues Of Global Geo-Financial Policy And Its Impact On International Financial Relations - Suleymanov Ilnur Radikovich, PhD (Periodica Journal, 2025)
This scientific article explores the pressing challenges faced by global geo-financial policy and their impact on international financial relations. The paper analyzes geopolitical tensions, trade conflicts, and strategic measures influencing the global economy. The research identifies key trends and offers recommendations for the sustainable management of international financial relations
Keywords: financial policy; international financial relations; geopolitical tension